Math Home
Proof Writing

Let \(P(i)\) be a statement for \(i = 1, 2, 3, \dots.\) A proof by induction is helpful when you want to prove \[\bigcap_{i=1}^\infty P(i)\] In other words, you want to prove that the statements \(P(i)\) are simultaneously true for all numbers \(i.\)

A proof by induction is a proof using the following strategy:

Once the base case and inductive step are proved, then the statements \(P(i)\) are proved for \(i = 1, 2, 3, \dots.\) This is because \(P(1)\) was proved, and since \(P(i) \rightarrow P(i+1)\) was proved, \(P(1) \rightarrow P(2)\) implies \(P(2)\) is a tautology (since \(P(1)\) is a tautology). Since \(P(2)\) is a tautology and \(P(2) \rightarrow P(3),\) \(P(3)\) is a tautology. Proceeding this way, the truth of all of the statements follows.

Example

Claim: For \(i \geq 1,\) \[\sum_{j=1}^i j = \frac{i(i+1)}{2}\]

Proof: When doing a proof by induction, it is good to state what strategy you are using to avoid confusing the reader. This will be a proof by induction.

Base case: First let \(i = 1.\) The sum is \[\sum_{j=1}^1 j = 1\] The fraction is \[\frac{1 \cdot (1+1)}{2} = 1\]
Inductive step: Assume that for some number \(n \geq 1,\) \[\sum_{j=1}^n j = \frac{n(n+1)}{2}\] We need to show the claim for \(n+1.\) When we plug in \(n+1,\) the claim becomes \[\sum_{j=1}^{n+1} j = \frac{(n+1)(n+2)}{2}\] First, rewrite the sum. Then use the inductive hypothesis. \begin{align} \sum_{j=1}^{n+1} j & = \left( \sum_{j=1}^n j \right) + (n+1) \\ & = \frac{n(n+1)}{2} + (n+1) \end{align} By getting a common denominator and combining like terms, one can show \[\frac{n(n+1)}{2} + (n+1) = \frac{(n+1)(n+2)}{2}\] which proves the claim.